PERAN LITERASI BAHASA DALAM MENINGKATKAN KEMAMPUAN NUMERASI SISWA PADA MATA PELAJARAN MATEMATIKA - Atiqah Shabirah Munthe; Heryanti, Najwa Dwi; Br Sembiring , Ega Emeysadella; Br Tarigan , Alya Andani Rahman; Febriana, Ika (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is motivated by the low level of students’ literacy and numeracy skills in Indonesia, which is influenced by a learning culture that is still oriented toward textbooks and the limited implementation of pedagogical strategies that support higher-order thinking skills. The purpose of this study is to analyze and describe the literacy and numeracy competencies of eighth-grade junior high school students systematically. This research employed a quantitative descriptive method involving 30 students selected through purposive sampling. Data were collected using a validated Likert-scale questionnaire covering indicators of conceptual understanding, information interpretation, data analysis, and decision-making. The data were analyzed using descriptive statistics, including mean scores and percentages. The results indicate that the overall average score of students’ literacy and numeracy skills is 63,6%, which falls into the moderate category. Students’ literacy skills are relatively higher, particularly in conceptual understanding (72,3%) and information interpretation (68,1%), while numeracy skills remain lower, especially in data analysis (58,7%) and data-based decision-making (55,2%). These findings reveal a gap between students’ ability to understand textual information and their ability to process numerical and visual data. Therefore, improvements in instructional practices are needed, particularly those that emphasize analytical thinking and problem-solving skills in mathematics learning.